2016
DOI: 10.1017/s1431927616010047
|View full text |Cite
|
Sign up to set email alerts
|

Monochromated Low-Dose Aberration-Corrected Transmission Electron Microscopy of Diamondoid Carbon Nanothreads

Abstract: Carbon nanothreads are the first in a new class of one-dimensional sp 3 carbon nanomaterials that was recently discovered through compression-induced polymerization of benzene in a Paris-Edinburgh cell [1]. Their diamond-like structure is predicted to have interesting mechanical properties that are on par with or greater than carbon nanotubes [2]. In addition, the solid-state synthesis is entirely driven by kinetic control and devoid of waste, which may open up new routes to fabricate efficient carbon nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…X-ray and electron diffraction experiments reveal symmetric two-dimensional spot patterns that provide compelling evidence for hexagonal single crystal packings hundreds of microns across of carbon (and carbon nitride) nanothreads that are spaced ∼6.5 Å apart, in good agreement with the spacing predicted by modeling of degree-6 nanothreads . The threads and their hexagonal packing are evident in transmission electron microscopy (TEM) imaging as well. , However, although NMR spectroscopy has revealed that nanothreads consist primarily (75–80%) of sp 3 -bonded carbon, the details of the chemical structure along their length are not yet understood. Fifty different degree-6 nanothread structures with 6 sp 3 -carbons per benzene formula unit (Figure ) have been enumerated by theory .…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…X-ray and electron diffraction experiments reveal symmetric two-dimensional spot patterns that provide compelling evidence for hexagonal single crystal packings hundreds of microns across of carbon (and carbon nitride) nanothreads that are spaced ∼6.5 Å apart, in good agreement with the spacing predicted by modeling of degree-6 nanothreads . The threads and their hexagonal packing are evident in transmission electron microscopy (TEM) imaging as well. , However, although NMR spectroscopy has revealed that nanothreads consist primarily (75–80%) of sp 3 -bonded carbon, the details of the chemical structure along their length are not yet understood. Fifty different degree-6 nanothread structures with 6 sp 3 -carbons per benzene formula unit (Figure ) have been enumerated by theory .…”
Section: Introductionsupporting
confidence: 58%
“… , Many of the pure degree-6 and pure degree-4 nanothread structures have approximately the same diameter and thus cannot be easily distinguished from each other or from mixtures of both degrees merely by geometric packing considerations, although detectable differences in lattice constants are expected in certain cases . Uniform “beading” patterns parallel to the nanothread axes and ∼15 nm in length (i.e., ∼100 carbon bond lengths) are observed in TEM images, suggesting that local order can be present over at least this distance …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the alignment and optimization of the STEM for EELS measurements were performed in areas away from the regions of interest to prevent preirradiation damage. Additionally, the electron beam was blanked before and after the EELS measurements to further protect the sample. …”
Section: Methodsmentioning
confidence: 99%